Leprosy: Effects on the Bearer’s Sexuality - Santos, Tatiana Maria Melo Guimarães dos (2010)
Studies related to leprosy give little attention to human affairs, feelings or experiences along the way, therefore, this paper aims to describe the effects leprosy has on the sexuality of leprosy patients and analyze the aspects which involve the sexuality of the bearer. This is a descriptive study with qualitative approach, developed at the “Centro Maria Imaculada”, which provides assistance to leprosy patients in the prevention, diagnosis, treatment and rehabilitation, in Teresina-PI. A series of semi-structured interviews was used as an instrument so as to produce data; they were analyzed according to Minayo’s Content Analysis. Analysis of the reports resulted in the emergence of four categories: changes in sexual activity after leprosy diagnosis, fear of diseasetransmission through sexual contact, feelings of inferiority, and changes in family’s daily life. The extent of suffering caused by the disease in the group of interviewed people was noticed, and so were the changes brought about in their sexual life caused by the disease, preventing bearers from experiencing an active sexual life, be it due to organic and/or psychological matters.